Kansas PRIDE 2012 Annual Review - Kahl, Dan; Rice, Trudy; Menon, Jaime (My University, 2012)
Summary of the 2012 actiivities of the Kansas PRIDE program and affiliated communities.
Keywords: Administrative and Research Reports; Community Development